Analysis of Employment in Republic of Croatia and Selected Member States of European Union According to Economic Activity (Vallis Aurea, 2016)
Employment is very important for the development of every country. Without jobs and employees there is no development of anything. Therefore, it is extremely important that each country take into account the employment of its citizens.Employment is an agreement between an employee and an employer that the employee will provide certain services on the job in the return for compensation.For the purpose of the work it has been conducted a detailed analysis of the employment in selected European Union Member States in the period from 2002 to 2012. It has been analyzed the employment according to economic activity. The analyzed countries are the Republic of Austria, the Republic of Bulgaria, the Czech Republic and the Republic of Croatia.The aim of the work is to show that there were differences in structure between the observed countries.